Nanodiamond thin films on titanium substrates - Growth and electrochemical properties - Hian, L; Grehan, K; Compton, R; Foord, J; Marken, F (2003)
A new type of electrically conducting nanosized diamond film deposit is grown on titanium substrates in a microwave plasma chemical vapor deposition process. The deposition process occurs at 80 Torr in a helium atmosphere with only hydrogen (1.95%) and methane (0.73%) admitted and yields a deposit growing approximately 0.5 μm h-1 thick. Electron microscopy indicates the formation of nanosized diamond platelets. The electrochemical properties of nanodiamond when immersed in aqueous electrolyte solution are explored for the Fe(CN)63-/4- system, the Ce4+/3+ system, the oxidation of hydroquinone, ascorbic acid, and the oxidation of dihydronicotinamide adenine dinucleotide. Compared to boron-doped diamond materials, nanodiamond is a highly active electrode material with very low overpotentials for all redox systems studied. For ascorbic acid, diffusion-controlled oxidation is detected at potentials approximately 0.5 V more negative compared to those observed at boron-doped diamond electrodes. The electrical conductivity, high surface reactivity, and electrochemical characteristics are explained in terms of many defects and active surface sites.